Kepemimpinan Situasional Pengurus Besar Himpunan Mahasiswa Islam (Studi Kasus Kepemimpinan HMI Masa Akbar Tanjung 1972-1974) - Nasrullah, Muhammad; A, Azhari (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Akbar tanjung is one of HMI members who could socialize with everyone easily without differing each other. His great personality and qualified ideas influenced by Nurcholis Majid encourage him to be known in whole society as a reformist and a pluralistic person from HMI and Youth community. His bright ideas have born many organizations such as Cipayung Community, KNPI and AMPI. In addition, this essay will describe how the situational leadership of Akbar Tanjung leads PB HMI between 1972 and 1974 and also supporting factor of his success during his period. The method used in this research is qualitative descriptive using deepen interview method and literature study. Analysis research said that the leadership of Akbar Tanjung could complete the situational leadershipparameter and his success to lead this organization supported by his capable communication skill and his good attitude while coordinating with other youth organizations. Moreover, this research shows that his leadership has proven the influence and could be adopted by the following leader.